Arnao. Origin of the industrial villages.: Article - López del Campo, Borja (Geographicalia, 2023)
The area around Arnao (Castrillón, Principality of Asturias) is known thanks to the installation of the Real Compañía Asturiana de Minas (RCAM), first as a mining company and then as a zinc producer. A productive history of more than 170 years that transformed a rural environment into the cradle of the industrialisation of the Principality of Asturias and Spain. It went through several stages in terms of land occupation, firstly through the construction of the manufacturing elements, and then through the construction of various dwellings and associated infrastructures.